Physical Activity Patterns in People With Inflammatory Arthritis Indicate They Have not Received Recommendation‐Based Guidance From Health Care Providers - Lauren M. Freid; Alexis Ogdie; Joshua F. Baker (ACR Open Rheumatology, 2020)
Objective Objectives of this study were to describe exercise patterns among patients with inflammatory arthritis (IA) in four recommended domains (Aerobic, Resistance, Flexibility, Balance), identify exercise barriers and facilitators, and explore patients’ perceptions of interactions with rheumatology providers about exercise. Methods Patients with IA at a single academic medical center were invited to complete a survey about exercise. Patients were recruited for a paper‐based survey prior to appointments or a web‐based study through the electronic health record if they had been seen in the practice within the past year. Respondents reporting minimum aerobic exercise plus at least one other domain were categorized as “Active,” and the remaining as “Inactive.” Survey responses were compared between groups. Results Of 1113 invited, 108 completed the survey. Among these, 60 (56%) reported aerobic exercise, 44 (41%) flexibility, 42 (39%) resistance, and 18 (17%) balance. Forty‐three (40%) were categorized as active, 65 (60%) inactive. The active group had lower body mass index, lower reported disease activity, and fewer comorbidities. Active patients reported more self‐efficacy, prioritized exercise, improved energy, exercising for weight control, and exercise before arthritis diagnosis (all P < .05). The inactive group cited finances, pain, fatigue, and potentially worsening arthritis as barriers (all P < .05). Most understood the benefits of exercise. Few perceived that exercise recommendations were addressed by their providers. Conclusion Approximately half of patients reported regular aerobic exercise; fewer regularly engaged in other types of physical activity. Patients do not perceive they have received exercise guidance from providers, which suggests an opportunity for more prescriptive exercise discussions.